Forest biodiversity: importance of species composition studies - Ibrahim, Faridah Hanum (Universiti Putra Malaysia Press, 2015)
The vision of the Malaysian National Policy on Biological Diversity 1998 which states "to conserve Malaysia's biological diversity and to ensure that its components are utilised in a sustainable manner for the continued progress and socio-economic development of the nation" indicates that Malaysian forests harbour a very large portion of the nation's biodiversity and that forests have an important role to play in the country's socio-economic development and environmental stability. Thus, the degradation of the nation's biological diversity would have grave repercussions on the economy, environment and people. In the forestry sector, biological diversity not only provides timber and non-timber goods but also numerous other ecological services such as environmental stability which includes carbon sequestration, maintenance of hydrological regimes and recycling of nutrients, besides providing a habitat for wildlife. Much of the nation's biological diversity has yet to be documented and strengthened with scientific investigations. Current forestry issues include deforestation, conservation, intensity of sampling, sustainable forest management, economic valuation of goods and services, carbon sequestration, payment for ecosystem services and reducing emissions from deforestation and forest degradation. The applications of species composition studies are many, but those that are pertinent to forest biodiversity works include the determination of minimum sampling size in forest inventory as inventories are expensive and laborious in nature, the use of indices that are comparable between forests, consideration of minimum diameter for enumeration and measurement so as not to lose important information on biodiversity and estimation of biomass and carbon sequestration. The importance of predicting and enhancing forest regeneration is crucial to determine the next course of action by foresters in enriching the forests besides helping it to grow better and faster for future yields. There is currently an underestimation on pricing of our timbers. Putting the correct timber species in the correct groups will thus help to increase revenue for the state governments. To date, some conservation works in the country have ignored the importance of some details in ensuring the success of the conservation programmes. These include re-introduction programmes of wildlife species and extension or creation of wildlife corridors. The justification for keeping conservation areas in the country, which are mainly forested areas, and the actions to be taken for its safe protection requires fundamental information such as species composition. Such information can be converted to suit many facets of understanding that deals with the current forestry and environmental issues such as economic value, carbon storage capacity and payment for ecosystem services